Effect of annealing atmosphere on structural and optical properties of CZTS thin films prepared by spin-coating - Akhanda, S; Matin, R; Bashar, MS; Sultana, M; Kowsar, A; Rahaman, M; Mahmood, ZH (Bangladesh Journal of Scientific and Industrial Research, 2018)
Copper zinc tin sulfide (CZTS) thin films were deposited by spin coating procedure of a sol-gel prepared from the solution of copper (II)chloride, zinc acetate, tin (II) chloride and thiourea in 2-methoxyehtanol followed by annealing under two different atmospheres viz. N2 gas and Sulphur (S) powder at 530 °C for 5 minutes. The effect of different annealing atmosphere on the structural and optical properties of the CZTS thin films were investigated. The X-ray diffraction study showed higher intensity peaks for films annealed under N2 gas ambient. SEM study revealed that the surfaces of the films in both cases are non-uniform. Films annealed in N2 gas atmosphere showed better absorption coefficient (exceeding 104 cm-1 in the visible region) than the sulphurized ones. The optical band gap (Eg) of the films were found to be in the range of 1.46 - 1.53 eV. Bangladesh J. Sci. Ind. Res.53(1), 13-20, 2018